Antioxidant activity of invasive species Solanum jamaicense - NIA YULIANI; RIDWAN RACHMADI; ADE AYU OKSARI; IRVAN FADLI WANDA (Nusantara Bioscience, 2024)
Abstract. Yuliani N, Rachmadi R, Oksari AA, Wanda IF. 2024. Antioxidant activity of invasive species Solanum jamaicense. Nusantara Bioscience 16: 54-61. Solanum jamaicense Mill. belongs to the Solanaceae family and is categorized as an invasive species. The leaves of S. jamaicense own some of these compounds, which are known to contain several compounds, including phenolics, coumarins, and flavonoids, which have the potential to be a source of antioxidants. This study aims to determine the content of phytochemical compounds and antioxidant activity of the leaves of S. jamaicense. Phytochemical testing includes tests for alkaloids, flavonoids, saponins, tannins, steroids, and terpenoids. The total phenolic content was tested using tannic acid as a comparison by spectrophotometry. They tested the antioxidant activity of S. jamaicense leaf extract by using spectrophotometric method. The antioxidant activity of the extract is expressed in the value of 50% Inhibition Concentration (IC50). Based on the results of the phytochemical test, the ethanol extract of S. jamaicense leaves contains alkaloids, flavonoids, tannins, saponins, and steroids. The research showed that the total phenolic content was 59.953 mg.g-1 of the extract, and the antioxidant activity was intense, with an IC50 value of 10.41 mg.L-1 (active). S. jamaicense leaves ethanol extract has the potential as a source of natural antioxidants.